ASPEK PENGETAHUAN, SIKAP DAN KETERAMPILAN PADA RESPON PETANI TERHADAP UPJA DI KECAMATAN TOHO - Ellyta, Ellyta; Mulyati, Mulyati; Kurniawan, Hery Medianto; Ekawati, Ekawati (Jurnal Social Economic of Agriculture, 2019)
The use of agricultural tools and machinery has become a primary needs of farmers in processing and increasing their farming production, this activity encourages the emergence of agricultural tools and machinery service unit (UPJA) that has an intention in assistaining farmers in achieving time and energy efficiency and also in order to overcome scarcity of farmer resources in processing their farming. However, the delayed development of UPJA in several regions has encouraged this research in order to analyze farmers' responses to the use of agricultural tools and machinery service unit. Research method: This study was conducted at the Bukit Raya UPJA Village Pak Leheng Toho District from January - March 2018. This research used the descriptive analysis data, which was displayed in table form with several categories that have been determined based on aspects of knowledge, attitude, and skills. Response measurements were carried out using a Likert scale (scoring) with a score of 1-5. The results of the all of the farmer showed that the response analysis from the aspects of knowledge, attitude, and skills of UPJA Bukit Raya amounted to 3.48 in the good category, which means that farmers generally gave a good respond to the existence of the UPJA Bukit Raya Village, in Pak Leheng Village, Toho District.Keywords: Agricultural Machinery, Farmer Energy Efficiency, Likert Scale